156k views
4 votes
Solve the equation below

Solve the equation below-example-1
User Skrebbel
by
4.3k points

2 Answers

6 votes

Answer:

662

Explanation:

2((11x11x11)-(10x10x10))=

2(1331-1000)=

2x331=

662

User Gundu Bandgar
by
4.5k points
3 votes

Answer:

662

Explanation:

First, do what is in the parenthesis. Since they are exponents, you go from left to right (PEMDAS).

11x11x11= 1331

10x10x10= 1000

So, now that you have solved the exponents, you should substitute them in to the original equation:

2(1331-1000).

In the parenthesis: 1331-1000= 331

that leaves us with 2x331.

The answer is 662.

User John Sparwasser
by
5.2k points